A quantitative analysis of German success factors during the 1944 razzia in Rotterdam - Wachlin, Seyla (Student Undergraduate Research E-journal!, 2015)
In this paper we quantitatively analyze which factors led to the success of the razzia that took place in Rotterdam in 1944. We show that the factors which made people less likely to evade capture were the use of surprise and the creation of a feeling of fear. Factors which made people less likely to evade and also less likely to escape after being captured were the use of misinformation and the creation of a feeling of powerlessness. We also found that, counter to expectations, a person’s demographic background did not impact the success of this razzia.